2020
DOI: 10.5194/amt-13-853-2020
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent satellite and ground-based lightning observations from the Optical Lightning Imaging Sensor (ISS-LIS), the low-frequency network Meteorage and the SAETTA Lightning Mapping Array (LMA) in the northwestern Mediterranean region

Abstract: Abstract. The new space-based Lightning Imager (LI) onboard the Meteosat Third Generation (MTG) geostationary satellite will improve the observation of lightning over Europe, the Mediterranean Sea, Africa and the Atlantic Ocean from 2021 onwards. In preparation for the use of the upcoming MTG-LI data, we compare observations by the Lightning Imaging Sensor (LIS) on the International Space Station (ISS), which applies an optical technique similar to MTG-LI, to concurrent records of the low-frequency (LF) ground… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
5
16
0
Order By: Relevance
“…In this paper EUCLID and ISS-LIS lightning observations are correlated using data from 1 March 2017 until 31 March 2019 as observed within the EUCLID domain and limited to 54 • north. The ISS-LIS detects optically bright discharges, such as return strokes and in-cloud discharges inducing a rapid change in the electric field (Goodman et al, 1988). Those rapid changes in the electric field are exactly the features detected by EUCLID.…”
Section: Methodsmentioning
confidence: 62%
See 4 more Smart Citations
“…In this paper EUCLID and ISS-LIS lightning observations are correlated using data from 1 March 2017 until 31 March 2019 as observed within the EUCLID domain and limited to 54 • north. The ISS-LIS detects optically bright discharges, such as return strokes and in-cloud discharges inducing a rapid change in the electric field (Goodman et al, 1988). Those rapid changes in the electric field are exactly the features detected by EUCLID.…”
Section: Methodsmentioning
confidence: 62%
“…An extra region is outlined in Fig. 7 covering Corsica, corresponding with the region investigated by Erdmann et al (2020) in which ISS-LIS flashes are matched against those observed by the ground-based Météorage network during an approximately 1-year period from 1 March 2017 until 20 March 2018. Applying analog flash matching criteria as in Erdmann et al (2020) over the Corsica area, i.e., strokes and pulses are matched to ISS-LIS groups using a 1.0 s temporal and 20 km spatial criterion, P (ISS-LIS|EUCLID) becomes 59.7 % in this study, which is similar to the 62.4 % found in Erdmann et al (2020).…”
Section: Flash Levelmentioning
confidence: 91%
See 3 more Smart Citations